(3QSGdI(B[(3aj Gdbhd(B] (3aj GdfaS GdeNJUQ ef cdGe CQSWh hCadGWhf hSGFQ GdadGSaIs - (3jYbhH Hf ESMGb Hf GdUHGM GdcfOj, CHh jhSa,J (B260 (3g` s
(3ChdgG (B:s
(3SQOc (B[(3NWGc(B] (3dOQc GdMb hCYGfc Ydi fjd eSJhYQGJg CdN s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B195 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B244s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B7 - (3U (B218 s
(3eUOQ GbJfGA GdCUd (B:s
(3eLdS ThQGi edi WgQGf (B(6/1373) s
Keywords: (3GdadSaI hGdefWbs